O ruchu częściowo bezinercyjnego zachowawczego układu mechanicznego - Szadkowski, A. (Engineering Transactions, 1968)
The paper deals with a strongly nonlinear mechanical single degree of freedom dampless system with spring elements connected in series. The motion of this system has been investigated by considering the phase trajectories of mass and of connecting points between the springs. The given example illustrates various cases of the discontinuities of the phase trajectories constructed on the basis of the energy integral.